(untitled) (Italian Journal of Public Health, 2012)
Pathogens that are capable of infecting more than one host, more than one taxonomic order and wild hosts, all present a higher relative risk of (re-)emergence. A long environmental persistence gives pathogens a more selective advantage. In case of an emerging or re-emerging zoonosis, the prevalence of infection in animals and the exposure determine the incidence in humans. Human exposure to zoonotic agents depends on lifestyle and occupation (e.g., veterinarians and farmers are more at risk for zoonoses related to livestock). Efforts to increase awareness, provide information on prevention, and apply biosecurity are essential. Moreover, a substantial decline in the incidence of human disease implies the prevention, the control or the elimination of zoonoses in the animal compartments. The only way to prevent health hazards is to adapt the existing systems of health governance at global, regional, national and local levels in a harmonised and coordinated manner. To achieve such a goal, the One Health strategy was recently developed to expand interdisciplinary collaborations and communications on all aspects of health care for humans and animals, veterinary, human medical, public health professionals and stakeholders....